Application of PCR-HRM method for microsatellite polymorphism genotyping in the LDHA gene of pigeons (Columba livia). - Magdalena Jedrzejczak-Silicka (Public Library of Science (PLoS), 2021)
High-resolution melting (HRM) is a post-PCR method that allows to discriminate genotypes based on fluorescence changes during the melting phase. HRM is used to detect mutations or polymorphisms (e.g. microsatellites, SNPs, indels). Here, the (TTTAT)3-5 microsatellite polymorphism within intron 6 of the LDHA gene in pigeons was analysed using the HRM method. Individuals (123 homing pigeons) were genotyped using conventional PCR. Birds were classified into groups based on genotype type and the results were tested by qPCR-HRM and verified using sequencing. Based on the evaluated protocol, five genotypes were identified that vary in the number of TTTAT repeat units (3/3, 4/4, 3/4, 4/5, and 5/5). Sequencing have confirmed the results obtained with qPCR-HRM and verified that HRM is a suitable method for identification of three-allele microsatellite polymorphisms. It can be concluded that the high-resolution melting (HRM) method can be effectively used for rapid (one-step) discrimination of the (TTTAT)3-5 microsatellite polymorphism in the pigeon's LDHA gene.